Edukasi penyimpanan obat yang benar untuk meningkatkan keamanan penggunaan obat di masyarakat - Putri Rovita Sari; Ika Sutra Perwirahayu Aji Saputri; Vivi Rosalina; Rosi Hayyu Anjani (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Storing medicines in conditions that do not meet temperature requirements can compromise their stability, quality, and effectiveness, thereby increasing the risk of therapeutic failure and adverse effects. However, public knowledge regarding temperature-appropriate medicine storage remains limited. Purpose: To improve public understanding of proper medicine storage practices as a means to enhance medication safety. Method: This community service activity was conducted on May 28, 2026, from 09:00 to 10:00 WIB in Krajan Hamlet, Kedungputri Village, Ngawi Regency. The organizing team consisted of lecturers and students from STIKES Bhakti Husada Mulia Madiun. Forty residents of Krajan Hamlet, Kedungputri Village, Ngawi Regency, participated in the activity. The initiative aimed to educate the community on the importance of storing medicines correctly according to required temperatures. Information was conveyed through lectures, discussions, and question-and-answer sessions. Knowledge levels were assessed using questionnaires administered before (pre-test) and after (post-test) the educational session. Evaluation involved comparing pre-test and post-test scores, with findings presented descriptively to outline the community's understanding of proper medicine storage procedures and their benefits. Results: The results showed that the mean age of respondents was 36.8 years, with the majority (n=27; 67.5%) falling within the 31–40 age range. All knowledge indicators improved following the educational intervention. The number of respondents demonstrating a